Determination of Deep Well Using Resistivity Method in South Amanuban, Timor Tengah Selatan Regency, Indonesia - Supandi, Supandi (Indonesian Journal on Geoscience, 2021)
DOI:10.17014/ijog.8.2.255-264South Amanuban often experiences drought during dry seasons, because the area is composed of Quaternary deposits with plain topography. Therefore, this research aims to identify and to evaluate the Quaternary deposit of groundwater potential, and to determine the deep well points in South Amanuban. The study utilized the geo-electrical method with the resistivity value approach to find high resistivity soils as aquifer layers. In addition, the deep well points are determined based on consideration of the aquifer positions from the resistivity analysis. The results show that aquifer positions are found in the limited zone of 50-150 m depth with lense shapes that are not related to each other.